Pyrene‐Based Small‐Molecular Hole Transport Layers for Efficient and Stable Narrow‐Bandgap Perovskite Solar Cells. Issue 10 (8th September 2021) - Gómez, Paula; Wang, Junke; Más-Montoya, Miriam; Bautista, Delia; Weijtens, Christ H. L.; Curiel, David; Janssen, René A. J.
Abstract : Lead–tin (Pb–Sn) hybrid perovskite materials possess ideal narrow bandgaps (1.2–1.4 eV) for efficient single‐junction and tandem solar cells. Poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) is commonly used as hole transport layer (HTL) for Pb–Sn perovskite solar cells (PSCs), despite its poor stability with these perovskites. Here, two new octacyclic heteroaromatic molecules, pyrenodiindole (PDI) and pyrenodi‐(7‐azaindole) (PDAI), are presented as the HTL for narrow‐bandgap (1.23 eV) p–i–n Pb‐Sn PSCs. The self‐assembled reciprocal hydrogen‐bonded solid‐state structure of PDAI bestows robustness compared to PDI, making it less vulnerable in processing the perovskite film on top, and improves the reproducibility of device fabrication. Transient photocurrent measurements and light‐intensity‐dependent device characteristics indicate that PDI and PDAI possess similar hole extraction properties to PEDOT:PSS. As a result, similar open‐circuit voltages and fill factors are obtained in the PSCs. Interestingly, the use of thin PDI and PDAI as HTL in PSCs changes the optical interference and reduces parasitic absorption in the near‐infrared region, resulting in an improved short‐circuit current density. Consequently, a higher power conversion efficiency of 16.1% is obtained for PDI and PDAI, compared to 15.1% for PEDOT:PSS. In addition, the self‐assembled structure of PDAI led to a notable enhancement of device stability. Abstract : The control of molecular packing through hydrogen‐bond‐directed self‐assembly bestows robustness to the structure of hole transporting layers (HTL). A comparative study between two analogous pyrene‐based small molecules proves that self‐assembled HTLs benefit the solution processing of Pb–Sn perovskite solar cells and improve their efficiency and stability, outperforming poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS).